2007
DOI: 10.1172/jci29959
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression analysis in pregnant women and their infants identifies unique fetal biomarkers that circulate in maternal blood

Abstract: The discovery of fetal mRNA transcripts in the maternal circulation holds great promise for noninvasive prenatal diagnosis. To identify potential fetal biomarkers, we studied whole blood and plasma gene transcripts that were common to 9 term pregnant women and their newborns but absent or reduced in the mothers postpartum. RNA was isolated from peripheral or umbilical blood and hybridized to gene expression arrays. Gene expression, paired Student's t test, and pathway analyses were performed. In whole blood, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
1
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 28 publications
2
49
1
2
Order By: Relevance
“…Plasma cellfree RNA has been investigated in cancer patients (9)(10)(11)(12) and maternal plasma (13,14) and was assumed to be packaged in apoptotic bodies that give it stability in plasma (15). Studies of maternal plasma mRNA transcripts have focused mainly on transcripts that are exclusively expressed from the placenta (16)(17)(18) or on isolated plasma samples (19) and have not attempted to comprehensively study global fetal gene expression in vivo.…”
mentioning
confidence: 99%
“…Plasma cellfree RNA has been investigated in cancer patients (9)(10)(11)(12) and maternal plasma (13,14) and was assumed to be packaged in apoptotic bodies that give it stability in plasma (15). Studies of maternal plasma mRNA transcripts have focused mainly on transcripts that are exclusively expressed from the placenta (16)(17)(18) or on isolated plasma samples (19) and have not attempted to comprehensively study global fetal gene expression in vivo.…”
mentioning
confidence: 99%
“…Despite the placental barrier, there is significant evidence that fetal cells and biomarkers can be detected in maternal blood during pregnancy and for several decades after delivery. 16 However, it has also been shown that exposure of adult HSCs to human umbilical cord blood stem cells in vitro culture conditions promotes expansion and differentiation of HSCs. 17,18 This supports the hypothesis that exposure of maternal stem cells to fetal cells promotes their expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, it was postulated that the placental-expressed mRNAs were encapsulated within a syncytiotrophoblast-derived microvesicle (STBM), which gave RNase resistance to "free" fetal RNA in maternal plasma [20]. us, with the development of RNA markers, analysis of maternal plasma allowed the noninvasive monitoring of fetal gene expression in a multitude of physiological and pathological conditions [21]. e various possible pathways by which cfDNA/cfRNA is released into circulation have been shown in Figure 1.…”
Section: Source Of Cell-free Fetal Nucleic Acids (Cffnas) In Maternalmentioning
confidence: 99%